Effect of competence on the performance of employees of the Bogor City manpower office with motivation as a moderating variable - Aryata, I Made; Marendra, I Gede (Jurnal Mantik, 2025)
The Bogor City Manpower Office (Disnaker) is a government agency responsible for assisting the Mayor of Bogor in implementing regional authority in the fields of employment and transmigration. This study aims to analyze the effect of competence on employee performance, with motivation as a moderating variable. The research employed a quantitative approach using the Structural Equation Modeling (SEM) technique and involved 155 respondents. The SEM analysis consisted of the normality test, validity test, reliability test, moderation test, hypothesis testing, and goodness-of-fit evaluation. The results show that competence has a significant positive influence on employee performance (p = 0.000; C.R. = 4.127), supporting H1. Meanwhile, motivation does not have a significant direct effect on employee performance (p = 0.202; C.R. = –1.276), leading to the acceptance of H2. However, motivation significantly strengthens the relationship between competence and performance (p = 0.015; C.R. = 2.441), thereby rejecting H3. The model fit indices (?² = 93.77; RMSEA = 0.08; CFI = 0.91; TLI = 0.89) indicate that the SEM model demonstrates acceptable structural validity. These findings confirm that competence is a key driver of employee performance and that motivation enhances its effectiveness. Therefore, developing both competence and motivational support is essential for improving performance in public sector institutions.